Johanne Gagnon : l’impasse de l’imaginaire - Verdier, Jean-Émile (CV Photo)

(untitled) (Les Productions Ciel variable, 1999)
Summary Fonds culinaire is a photographic stock-taking of the physical congestion caused by kitchen objects. Since 1990, Johanne Gagnon has been working on creating a legitimate description of a kitchen from an exact knowledge of everything that is likely to define the function of this room in the house, from its foundations to the colour of the tiling to the space that each object in it takes up. The work shows, in a fictional representation, the impossibility of projecting a future reality from an exact knowledge of a reality that is lived, perceived, and felt, because such a representation can only result in the representation of a future reality that is frozen and closed to the unforeseen. Fonds culinaire forces this realization, from which a more general conclusion can be drawn: the imaginary cannot be inferred from the real.